FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS MAHASISWA - Wardati, Emi (STIE Totalwin Semarang, 2014)
The purpose of this research is to analyze the influence of the quality of teaching, Â and the quality of service in conjunction with satisfaction and loyalty student of the STIE Totalwin Semarang. Data were obtained through a questionnaire and analyzed using Structural Equation Modeling (SEM). The results showed that student loyalty can be built from a variable learning through student satisfaction and student loyalty can also be constructed from the quality of service through student satisfaction.